IMF Survey, Volume 37, Issue 02. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2008)
Financial market turbulence; world growth; global outlook; financial market outlook; subprime fallout; writedowns; risk management; credit rating agencies; prudential oversight; liquidity management; risk measurement; public debt; subprime crisis; central bank liquidity; financial turmoil; open market operations; liquidity; securities valuation; risk modeling; Ghana; bond issue; Niger; debt relief; Millennium Development Goals; fiscal management; fiscal transparency; Latin America; Davos.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet